A study on menopausal experiences in Malaysian women in Kelantan - Mahmood, Nik Mohamed Zaki Nik (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
Menopause is associated with numerous transient typical and atypical sympto~s. ·It is believed that Asian women suffer more of the atypical symptoms and fewer, and with lesser severity, the typical psychological and vasomotor symptoms than the western women. This study reports the incidence and nature of menopausal symptoms in Kelantanese women and the self-care actions taken by them. A semi-structured, self-administered questionnaire'. was administered to 326 I) ~ . postmenopausal women (aged, 57.01 ± 6.~8 (SD) years) residing in th~ state of Kelantan. The· subjects comprised of naturally menopaused,· healthy women. Women with - uncontrolled diabetes and h)ipertension were not included. Descriptive statistic.al analysis was performed ~n the data using SPSS pro~amme. Mean age at menopause was 49.4 ± 3.4 (SD) years while both the mode and median were 50 years. The mode for the number of symptoms complained by each woman was 8 (range 0- 16). The incidences for atypical symptoms was; tiredness (79.1 %), reduced concentration (77.5%), musculo-skeletal aches (70.6%) and backache (67.7%). Night sweats (53%), headaches (49.4%) and hot flushes (44.7%) were the typical vasomotor symptoms, whereas mood swings (51%), sleep problems (45.1%), loneliness (41.1%), anxiety (39.8%), and crying spells (33.4%) were the main psychological symptoms. Majority of the women reported reduced vaginal secretion (50.9%). The commonest coi tal frequency was approximately 2-4 times per month (49.7%). Overall, 42.3% reported a decrease in the frequency of sexual activity postmenopausally. Over twothirds (69%) of the women reported either reduced (39%) or absent (29.6%) sexual desire or interest. A similar pattern was also reported for libido. Varying degree of dyspareunia was reported by 34% of the . women. Some women (23.3%) had noticed that their spouses' sexual interest in them had reduced compared to before menopause. A small percentage (7 .1%) reported that their vagina was not able to accommodate comple~ely an erect penis. A small percentage (2.1%) admitted to having sexual problems, which had an affect on their marital relationship and another group (9.5%) had spouses With sexual problems. A quarter of the women though~ their sexuality could be improved while . another quarter thought otherwise. More than half (52.6%) did not take any action to improve their sexuality. Those who did, took HRT, "Jamu", Evening Primrose Oil, Royal jelly, did regular exercises and controlled their diet. The percentage of women taking self-care actions depended up<?n the symptom, and ranged from 47.7% for reduced concentration to 100% for crying spells and anxiety. Their self-care actions included taking traditional medicine, alternative medicine, prescribed medications, getting actively involved in community work, and having peer support. More than half (55%) did not seek any advice regarding their menopause. Those who did, mainly approached their friends. Some 13% of women were not aware of the menopause when it occuned.